R & D Spillovers and Recipient Firm Size - Acs, Zoltan J.; Audretsch, David B.; Feldman, Maryann P. (The Review of Economics and Statistics, 1994)
The findings in this paper provide some insight into how small firms are able to innovate. Using a production function approach to relate knowledge generating inputs to innovative output, the empirical results suggest that small firms are the recipients of R&D spillovers from knowledge generated in the R&D centers of their larger counterparts and in universities. Such R&D spillovers are apparently more decisive in promoting the innovative activity of small firms than of large corporations. Copyright 1994 by MIT Press.